PENDEKATAN PEMBELAJARAN DAN TINGKAT USIA MENINGKATKAN KETERAMPILAN BERMAIN SEPAKBOLA - Waluyo, Waluyo (Jurnal Phederal Penjas, 2008)
The main purpose  of this reaserch  was to examine  deference  of the effect  of learning approach   and age level to an efficient  and effective soccer playing  skill  which  is suitable for  children's  acceleration  of development  stages, is needed.  The outcome  of such research is applicable for  the soccer skill learning for  children at the school  age level  or at football schools.   The  research   employs  the  experimental   method  with  2 x  2   factorial    design. Fourthy  male  students  of elementary  school  taken by purposive    random  sampling,   were classified  into four  cells.  Data of soccer skill  are taken the MorChristian   General  Soccer Ability  Skill "Test Battery.  The treathment  was conducted  three times  a week  during  eight weeks. Test were administered prior  to and after eight weeks.  The Research  concludes  that the playing  approach  model has better result than the practicing  approach  one does to the soccer  learning  skill.   The result of learning of children  at the l O-to-l Zyears-old  age level is better  than those at the  7-to-9- years-old  age level:  The implications  of the research  is the necessity  of applying  the playing  approach   at any grade  of the elementary  school  andsoccer school.  Soccer  schools  should  choose students   starts at the age a of 10 to 12 years   .old.